Condylar cartilage growth. A literature review - Romero Peláez, Claudia Margarita (2018)
The mandibular condyle is a secondary cartilage characterized by its response to functional and mechanical loads; its repeated stimulation triggers a serie of events that seems to increase the number of replicating mesenchymal cells. In this literature review we present fundamental findings to understand the factors that condition condylar growth. The following associated topics were analyzed: embryology, genetic and environmental influence, function as a center of growth and bioengineering applied to this field. It was evidenced in the reviewed literature that the condyle acts as the main center of regional adaptive growth and the regulation of development is determined by genetic and epigenetic factors that modify the expression of transcription and growth factors.